Ecological Risk Assessment for Chlorpyrifos in Terrestrial and Aquatic Systems in North America - Giesy, John P.; Solomon, Keith R. (Reviews of Environmental Contamination and Toxicology, 2014)
Ecotoxicology; Environmental Management; Waste Management/Waste Technology; Chlorpyrifos; Terrestrial systems; Aquatic systems; Ecological risk assessment